Underweight and Its Predictors Among Patients on Anti Retroviral Therapy at Selected Health Facilities of Addis Ababa, Ethiopia, 2020 - Sahile AT (Dove Medical Press, 2021)
Addisu Tadesse Sahile,1 Solomon Muluken Ayehu,2 Selamawit Fekadu Fanta3 1Department of Public Health, Unity University, Addis Ababa, Ethiopia; 2Department of Emergency, Menelik II Referral Hospital, Addis Ababa, Ethiopia; 3Department of ICU, Saint Peter Specialized Hospital, Addis Ababa, EthiopiaCorrespondence: Addisu Tadesse Sahile Tel +2519 1209 6667Email sahdis91@gmail.comObjective: The study aimed at assessing the prevalence of underweight and its predictors in patients on ART, in health facilities of Addis Ababa, Ethiopia, 2020.Methods: A multi-center-based cross-sectional study was conducted among 319 patients on ART selected on the basis of stratified sampling method in Addis Ababa from July 01 to August 30, 2020. An interviewer-administered structured questionnaire was used for collection of the data, after which informed consent was obtained from all the included participants. Descriptive statistics for the summarization of the data was used. Binary (Bivariate and multivariate) logistics regression was applied for the identification of predictors of underweight and its strength of association with their respective 95% confidence intervals and less than 5% p-values as statistically significant association.Findings: The prevalence of underweight among patients on ART was 19.1% (95% CI: 15.0– 23.9%), while more than one-tenth (14.4%) of the participants were overweight (95% CI: 10.8– 18.8%). A higher level of Educational level, being married, widowed, divorced, a lower family size and poor ART drug adherence level were statistically significantly associated with an increased risk of underweight among patients on ART in the study settings (p< 0.05).Conclusion: Educational level, marital status, family size, and adherence status of the participants were identified predictors of underweight among patients on ART. The lower the educational level, lower family size, being either married, divorced, or widowed, having had of poor ART drug adherence level of the participants, the higher their risk of sustaining underweight. Concerned bodies were suggested to work over the identified determinants of underweight among patients on ART in the study settings.Keywords: underweight, predictors, ART